НЕВИКОНАННЯ ЗАКОННИХ ВИМОГ ЯК ФОРМА ПРОЯВУ ОБ’ЄКТИВНОЇ СТОРОНИ ПЕРЕШКОДЖАННЯ ДІЯЛЬНОСТІ НАРОДНОГО ДЕПУТАТА УКРАЇНИ АБО ДЕПУТАТА МІСЦЕВОЇ РАДИ - Ладнюк, Вікторія Ростиславівна (SUPREMANCE OF LAW, 2019)
The article examines the essence and legal nature of non-compliance with legal requirements as a form of manifestation of the objective side of interfering with the activities of a people’s deputy of Ukraine or a deputy of the local council. The author draws attention to the fact that non-fulfillment of claims should be considered as non-compliance of the relevant actions, and the commission of actions on which there is a prohibition or restriction. Failure to comply may only concern the lawful demands of a people’s deputy of Ukraine, a deputy of a local council, committee or temporary investigative commission of the Verkhovna Rada of Ukraine. At the same time, the legality of the claim is detetmined by: a) the content of the claim; b) the form and manner of expression (passing) the requirement. These features should be determined on the basis of other normative legal acts that regulate the rights and powers of people’s deputies of Ukraine, deputies of local councils, committees or temporary investigative committees of the Verkhovna Rada of Ukraine.